The Protective Effect of Vitamin E Against Genotoxicity of Lead Acetate Intraperitoneal Administration in Male Rat - Nadia AITHAMADOUCHE; Nesrine SADI; Omar KHAROUBI; Miloud SLIMANI; Abdelkader AOUES (Notulae Scientia Biologicae, 2013)
Lead is industrial pollutant that may have toxic effects on the male. The aim of this study was to further investigate the protective effects of vitamin E on lead acetate (Pb) induced reproductive toxicities and genotoxicity effects in male rat. Sexually mature male Wistar rats (weighing 120-160 g) were given Pb (20 mg/Kg) and vitamin E (600 mg/kg/rat) orally for 20 days. The sperm counts, sperm motility, sperm morphology, chromosomal aberrations, FSH, LH and testosterone levels, and histopathological changes in the testes of these rats, were investigated at the end of 20 days. Result revealed a statistically significant (p<0.01) increase in the number of abnormal sperm in treated animal. Lead acetate increased the percentage of chromosomal abnormalities. Significant decrease in LH, FSH, and testosterone were observed in treated group compare with the control. Pathological examination of testicular tissues showed degenerative changes of spermatogonia and spermatocytes to advanced degeneration and vacuolation. The observation, dealing that lead acetate can be considered as an environmental genotoxic and cytotoxic effect in male rat and may contribute in reduction of fertility. We recommended that it must be administered of vitamin E as a protective agent to reduce the genotoxic effect of lead in the somatic and germ cells.